FAMILY ETHNOPEDAGOGY IN THE FORMATION OF A CHILD’S ETHNOCULTURAL IDENTITY IN MODERN CONDITIONS - Goverdovskaya, Elena; Tatarinceva, Ekaterina; Dzhagaeva, Tat'yana; Alikhanova, Rovzat; Kharaeva, Leorena (Revista Inclusiones, 2020)
The present article examines the structure of ethnocultural identity; the factors influencing its formation; the peculiarities of Chechen identity and the use of methods of folk pedagogy for the development of ethnocultural identification of children. The relevance of the study is in the need to find the most effective pedagogical tools that form the ethnic and cultural identity of a child; encourage the development of the culture of interethnic communication; teach to respect both the native and foreign spiritual values and traditions. There is also a need to find opportunities to introduce all these methods in the daily routines of families and educational institutions.